Early and late bilingual processing of Spanish gender, morphology and gender congruency - Alarcón, Irma (Borealis – An International Journal of Hispanic Linguistics, 2020)
The present study investigates whether advanced proficiency-matched early and late bilinguals display gender agreement processing quantitatively and qualitatively similar to that of native speakers of Spanish. To address this issue, a timed grammaticality judgment task was used to analyze the effects on accuracy and reaction times of grammatical gender, morphology, and gender congruency of the article and adjective within a noun phrase. Overall results indicated no significant statistical differences between the native speakers and the two bilingual groups. Both early and late bilinguals displayed similar grammatical gender knowledge in their underlying grammars. A detailed examination of the congruency effect, however, revealed that the native speakers, not the bilinguals, displayed sensitivity to gender agreement violations. Moreover, the native and heritage speakers pattern together in accuracy and directionality of gender agreement processing: both were less accurate with incongruent articles than with incongruent adjectives, while the second language learners were equally accurate in both agreement domains. Despite having internalized gender in their implicit grammars, the late bilinguals did not show native-like patterns in real time processing. The present findings suggest that, for high proficiency speakers, there is a distinct advantage for early over late bilinguals in achieving native-like gender lexical access and retrieval. Therefore, age of acquisition, in conjunction with learning context, might be the best predictor of native-like gender agreement processing at advanced and near-native proficiency levels.